Developing Supplementary Speaking Material for Eighth Grade Students - Feri Ferdiyanto; Achmad Kholili (English Education Department, Postgraduate, Universitas Sultan Ageng Tirtayasa, Indonesia, 2022)
The objective of this study is focusing on developing supplementary speaking materials for the eighth grade students of junior high school. It is according on students’ need and their difficulties in mastering their speaking ability. This problem found in SMP Plus Al-Mashduqiah. Students felt very difficult to speak because they did not know how to pronounce the word. Moreover, the speaking material in the existing book that used by school are too limited in scope of speaking. In fact, textbook and workbook used by the eighth grade students SMP Plus Al-Mashduqiah only have little portion, making a supplementary speaking material is needed and crucial. This design of the development is research and development with the adaption of the development proposed by Borg and Gall (1983). The procedures employed in this study were need analysis, stating instructional goals, developing instructional material, expert validation, try-out and final product. The results indicate that speaking materials developed by the researchers are appropriate to use for eight-grade students in the school and the teachers, therefore, strongly recommend that it be used by the teachers in other school settings as well.